Synthesized f-MWCNTs/CS/PB for determination of manganese (Mn²⁺) in drinking water - Gilbert Ringgit; Shafquzzaman Siddiquee; Suryani Saallah; Mohammad Tamrin Mohamad Lal; Most Tahera Naznin (Springer-Verlag GmbH Austria, part of Springer Nature, 2023)
In this research, the manganese ion (Mn²⁺) in drinking water was detected using functionalized multiwalled carbon nanotubes (f-MWCNTs) and chitosan (CS) immobilised with Prussian blue. Drinking water that contained soluble manganese (Mn²⁺) became insoluble (Mn³⁺ and Mn⁴⁺) when water phytochemistry changed as a result of unpredictably high manganese emissions from human activities into the environment. Manganese toxicity has been associated with brain disorders and metabolic activity. Electrochemical parameters such as (0.1 M, pH 2) phosphate bufer saline supported 5 mM Prussian blue, scan rate=250 mV s −1, accumulation time=20 s, and volume 10 cm3 were optimized using the cyclic voltammetry method. The f-MWCNTs/CS/PB generated highest current signal followed by PB/AuE and AuE. The stability of f-MWCNTs/CS/PB showed less than 7% for repeatability and reproducibility. Also, f-MWCNTs/CS/PB/AuE was selective towards Mn²⁺ with no inferring activity detected. However, this sensor can only be kept for 14 days due to the decreased current signals. Diferential pulse voltammetry method was used to detect diferent amounts of Mn²⁺ ranging from 0.2 to 3 ppm under optimal conditions. The limit of detection (LOD) was found to be 2.60× 10–6 M, with correlation coefcient (0.2–1 ppm) y=0.0413x+0.0734, with R2=0.9679. The percent recovery of a drinking water sample ranges from 94.87 to 100.4%. The modifed electrode (f-MWCNTs/CS/PB/AuE) has various advantages for detecting Mn²⁺ in drinking water, including a simple procedure, less operating time, high sensitivity and selectivity